Pupil Transportation Management - Miller, Anthony R. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
The safest means of transportation in the United States is the school bus fleet. Each school day, over 350,000 school buses transport about 22,000,000 children ages 3 to 21--from wheelchair pupils to varsity football players--to and from school in weather conditions ranging from those for Fairbanks, Alaska, to those typical of Cave Creek, Arizona. Many school systems ignore their pupil transportation administrator, yet this individual often manages a great many people, controls a large budget, and handles some of the most sensitive issues of the school system. This book, containing 13 chapters, was written to call attention to the value and importance of the school bus transportation services. The chapters cover: (1) the challenge for pupil transportation; (2) transportation administration and management; (3) communications; (4) alternative fuels; (5) labor and contractor relations; (6) the bus driver; (7) routing and scheduling; (8) the role of the computer; (9) the transportation budget; and (10) inclement weather. The appendix contains 20 transportation job descriptions from the role of the director of transportation to the duties required of tire specialists. (KM)
Availability: Ramsburg and Roth Publishers, 1735-A Ide Court, Thousand Oaks, CA 91362 ($15.75).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administration; Bus Transportation; Elementary Secondary Education; Organizational Effectiveness; Program Administration; Safety; School Buses; Service Vehicles; Student Transportation; Books; Guides, Non-Classroom.